Advances in Multimedia Information Processing - PCM 2016 : 17th Pacific-Rim Conference on Multimedia, Xi an, China, September 15-16, 2016, Proceedings, Part II /: 17th Pacific-Rim Conference on Multimedia, Xi an, China, September 15-16, 2016, Proceedings, Part II. (2016) - Unknown
No abstract available